ANALISIS SEMIOTIKA MAKNA TOXIC RELATIONSHIP DALAM SERIAL DRAMA “YANG HILANG DALAM CINTA” - Kurniawan, Yoseph Wahyu (SEMIOTIKA: Jurnal Komunikasi, 2024)
Toxic relationship is a social issue that can occur in the real life, especially in an interpersonal relationship. This can be emphasized through the numbers of violence against couples in Indonesia which continues to increase from year to year. The issue of toxic relationship then tried to be raised through one of the drama series, namely "Yang Hilang dalam Cinta". The drama series originates from a true story that tells about the relationship between Rendra and Dara, as lovers who are trapped in a toxic relationship. This study then aims to determine the meaning of toxic relationship in the drama series "Yang Hilang dalam Cinta" through Roland Barthes' semiotic analysis. The research method used in this study is descriptive qualitative and also analyzed using Roland Barthes' semiotic theory whose elements consist of denotation, connotation and myth. The results of this study indicate that the interpersonal relationship between Rendra and Dara is at a fading stage, and the meaning of the toxic relationship contained in the drama series "Yang Hilang dalam Cinta" can be identified from excessive jealousy, poor communication, occurrence of physical or psychological violence, controlling behavior, possessive, manipulative, lack of support and power imbalance in a relationship.